Factors associated with confirmed measles among notified measles cases in Pahang, 2016-2020 - Daud, Mohd Rujhan Hadfi Mat (2021)
Background: Measles is an acute communicable vaccine preventable disease that has become the major concern of public health. Elimination of measles has been a goal for all countries under the WHO region. Malaysia has started Measles Elimination Program since 2004 however the incidence trend of measles in Malaysia has not make much improvement. Objective: The study aimed to describe the proportion of confirmed measles among notified measles cases, to describe the trend of incidence rate of measles and to determine the factors associated with confirmed measles among notified measles cases in Pahang from 2016 to 2020. Methodology: This was a cross-sectional study using secondary data year 2016 until year 2020 from SM2 e-measles from Pahang State Health Department. The study was conducted from November 2020 to April 202l. Relevant data were extracted from SM2 e-measles which is a measles surveillance system in Malaysia. The data were collected using proforma and were analysed using SPSS software version 27. The data were analysed using descriptive analysis, simple and multiple logistic regression. Result: A total of 2844 notified measles cases were included in this study in which the proportion of confirmed measles cases were 7.41%. The incidence rate of measles infection in Pahang from 2016 until 2020 were ranges from 13.51 to 50.97 per 1,000,000 population with fluctuating trend. The associated factor for confirmed measles that were found to be significant were being indigineous (AdjOR = 4.90), Background: Measles is an acute communicable vaccine preventable disease that has become the major concern of public health. Elimination of measles has been a goal for all countries under the WHO region. Malaysia has started Measles Elimination Program since 2004 however the incidence trend of measles in Malaysia has not make much improvement. Objective: The study aimed to describe the proportion of confirmed measles among notified measles cases, to describe the trend of incidence rate of measles and to determine the factors associated with confirmed measles among notified measles cases in Pahang from 2016 to 2020. Methodology: This was a cross-sectional study using secondary data year 2016 until year 2020 from SM2 e-measles from Pahang State Health Department. The study was conducted from November 2020 to April 202l. Relevant data were extracted from SM2 e-measles which is a measles surveillance system in Malaysia. The data were collected using proforma and were analysed using SPSS software version 27. The data were analysed using descriptive analysis, simple and multiple logistic regression. Result: A total of 2844 notified measles cases were included in this study in which the proportion of confirmed measles cases were 7.41%. The incidence rate of measles infection in Pahang from 2016 until 2020 were ranges from 13.51 to 50.97 per 1,000,000 population with fluctuating trend. The associated factor for confirmed measles that were found to be significant were being indigineous (AdjOR = 4.90), history of contact with measles cases (AdjOR = 14.03) and incomplete vaccination (AdjOR = 3.38). Conclusions: Ethnicity, history of contact with measles case and vaccination status were the factors associated with confirmed measles among notified measles cases. Aborigine vaccination coverage should be improved, and complete dose of measles vaccination should be a main target in reducing the incidence of measles and thus, target for measles elimination will be achievable.